Teller Service Satisfaction Level Analysis at BNI Undaan Surabaya Branch - Ahmad Ali Mahmud; Elok Damayanti (Jurnal Ekonomi, 2021)
This study aims to find out the analysis of the level of satisfaction of teller services at BNI Undaan Surabaya Branch by using the research dimension consisting of tangible (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (guarantee) and empathy (empathy). This research is a research that uses the approach qualitative, the technique used in this research is the method of questionnaires and data collection techniques through google form. Then using the gap analysis method and managed to find the gap score is - 0.48 with an average score of -0.096. The research subjects used were customers at BNI Undaan Surabaya Branch which amounted to 50 people. The results showed from 50 respondents known analysis of the quality of teller services to customers at BNI Undaan Surabaya Branch with a Very Dissatisfied attitude of 0%, Dissatisfied 0%, Dissatisfied 0%, Satisfied 9.6% and Very Satisfied 90.4%. Based on the results of the research can be interpreted the quality of service provided by the teller at BNI Undaan Surabaya Branch is Very Satisfied.